Penilaian Risiko Sistem Informasi Fakultas Teknik Universitas Diponegoro Menggunakan Metode Failure Mode Effect And Analysis Berbasis Framework ISO 27001 - Naniek Utami Handayani; Mochammad Agung Wibowo; Diana Puspita Sari; Yoga Satria; Akbar Romadhona Gifari (Diponegoro University, 2018)
The data leakage and misuse of information by unauthorized parties that had happened forces the protection of security of information system in the Faculty of Engineering Diponegoro University (SIFT UNDIP) to be improved. This research aims to identify the risks, to analyze security of information system management, and to determine risk priority in SIFT UNDIP. This research is conducted using Failure Mode Effect and Analysis method based on ISO 27001 framework. Analysis results show that there are 25 risk agents in SIFT UNDIP which are categorized into four types of assets. The highest risk in High Level Risk category is the risk of dependence on employees which has Risk Priority Number value of 80.